PELAKSANAAN PERJANJIAN PEMBIAYAAN KENDARAAN RODA EMPAT DENGAN JAMINAN FIDUSIA PADA PT. ACC FINANCE - Sebastian, Yuda; Lestari, Rika; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Consumer finance institutions help people in overcoming the limitations in purchasing power caused by the amount of revenue generated. The presence of the consumer finance institutions will greatly help the community. The legal basis for consumer financing agreement is an agreement between the parties based on the principle of freedom of contract, the agreement between the creditors and financial firms as part of consumers as debtors.The purpose of this study are as follows: First, to determine the form of the rights and obligations of the parties under the financing agreement four-wheeled vehicle with a fiduciary, Second, identify any obstacles encountered during the implementation of the rights and obligations of the parties took place, Third, to know the result law arising in the event of default in the credit agreement.This type of research used by the author is the empirical legal research, or known as sociological research. This research was conducted at PT. ACC Finance Pekanbaru and the population and the sample is legal and marketing staff of PT. ACC Consumer Finance Pekanbaru also implementing the agreement. In this study the data sources used, the primary data, secondary data, the data tertiary, technical data collectors in the study interview, observation, and literature study.From the research problem there are three main things that can be inferred First, both parties are acutely aware of their rights and obligations of each as agreed in the agreement of consumer finance, Second, in the implementation of the financing agreement consumers encountered various obstacles caused by negligence debtor, Third, all things legal act especially when borrowers are in default then the legal consequences, namely: compensation and cancellation of the agreement.Suggestions Author, First, in this case should creditors not only prioritize their dues but look at the state of the debtor and the debtor should not have been negligent in carrying out its obligations, the Second, the two sides are expected to carry out the feat contents of the agreement in good faith and the debtor to be more open and honest with the creditor will the problems that it faces.Keywords: Agreement, Debtors, Creditors, Implementation, Fiduciary